Implementasi Teknik Equivalence Partitioning pada Pengujian Aplikasi E-learning Berbasis Web - Agustian, Andrian; Andryani, Imas; Khoerunisa, Sita; Pangestu, Adjie; Saifudin, Aries (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Testing is a verification process carried out to determine the quality of a software. In this case data validation becomes necessary, because errors that occur can make the system not optimal and can harm the owner or user of the system. For example, a compilation error the user can upload any file on the system. This can make the system corrupt and this cannot be known and tested. Black Box Testing has 4 methods, namely Equivalence Partitioning, Pairwise Testing, Boundary Value Analysis and Error Guessing. Each technique has advantages. However, in this study the Equality method was chosen because it was considered the most suitable way to conduct testing on E-learning Applications at Pamulang University. This method returns the system by dividing the input space or range into 2, valid and invalid. Can be obtained trial results obtained. This research begins by determining the functionality that will transfer, determining the data to be contested, determining the input can consist of numerical values, range of values and files, conducting test experiments, documenting research results and repeating results. From the results of tests that have been done, it can be concluded that this device can be used properly and perfectly. However, this research was only carried out using a number of sample forms. For Temporary Devices this can be used properly without any obstacles.